2015
DOI: 10.1016/j.jpsychires.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Fear responses to safety cues in anxious adolescents: Preliminary evidence for atypical age-associated trajectories of functional neural circuits

Abstract: Adolescent anxiety is common and impairing and often persists into adulthood. There is growing evidence that adult anxiety is characterized by abnormal fear responses to threat and safety cues, along with perturbations in fear-related neural circuits. Although some of this work has been extended to adolescents, with promising results, it is not yet clear whether changes in these circuits across developmental age varies between anxious and non-anxious adolescents. Here we used fMRI to examine how age modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Our main contrast of interest for this task was the comparison between CS+ (unmatched) vs CS−, following previous studies that have reported AMG recruitment, mainly in adolescents, but in adult populations as well (Lau et al, 2011). This contrast has also been reported to engage other brain regions (Haddad et al, 2015). We cannot determine whether this lack of overall recruitment was due to habituation across our imaging session or if it was a task effect.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our main contrast of interest for this task was the comparison between CS+ (unmatched) vs CS−, following previous studies that have reported AMG recruitment, mainly in adolescents, but in adult populations as well (Lau et al, 2011). This contrast has also been reported to engage other brain regions (Haddad et al, 2015). We cannot determine whether this lack of overall recruitment was due to habituation across our imaging session or if it was a task effect.…”
Section: Discussionmentioning
confidence: 52%
“…We did not test for correlations with the SLp because it did not successfully recruit the AMG, contrary to previous results in the literature (Haddad et al, 2015; Lau et al, 2008). Our main contrast of interest for this task was the comparison between CS+ (unmatched) vs CS−, following previous studies that have reported AMG recruitment, mainly in adolescents, but in adult populations as well (Lau et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Studies of youth anxiety report greater conditioned fear responses to the CS+ in anxious children and adolescents relative to nonanxious peers, although there are some inconsistencies across measures (skin conductance responses (SCR); verbal fear ratings; Britton et al., ; Craske, Waters, Craske, Bergman, & Treanor, ; Lau et al., ; Waters, Henry, & Neumann, ). Responses to the CS− during acquisition are also higher in anxious compared with nonanxious youth (Britton et al., ; Craske, Waters, et al., ; Haddad, Bilderbeck, James, & Lau, ; Waters et al., ). One study did not find group differences (Pliszka, Hatch, Borcherding, & Rogeness, ) though this investigated anxiety in attention‐deficit hyperactivity disorder children, and another study found that group differences emerged in the absence of fear discrimination to the CS+ versus CS− in anxious children only (Liberman, Lipp, Spence, & March, ).…”
Section: A Review Of Information‐processing Factors Involved In Childmentioning
confidence: 99%
“…In these studies, differential conditioning is [71,76,77]. Although, some studies suggest that anxious youth show larger SCR and SR fear to both the CS+ and the CS-, a larger differential response is not reported [41,72,74,75]. Consistent with clinical evidence, anxious youth have been found to exhibit greater behavioral avoidance, as evidenced by higher rates of study attrition when confronted with an aversive US [41,73].…”
Section: Threat Conditioning and Extinction In Youth With Anxiety mentioning
confidence: 99%
“…Additionally, anxiety symptom severity was found to be associated with greater SR fear of stimuli [73]. As noted above for unaffected youth, several factors have been found to influence threat conditioning, including gender [78] and age-related neurobiological distinctions [75]. Unfortunately, there has been no examination of threat generalization or context conditioning in anxious youth.…”
Section: Threat Conditioning and Extinction In Youth With Anxiety mentioning
confidence: 99%